Romantic nostalgia as a resource for healthy relationships. (June 2022) - Evans, Nicholas D.; Juhl, Jacob; Hepper, Erica G.; Wildschut, Tim; Sedikides, Constantine; Fetterman, Adam K.
Nostalgia is an emotion that confers psychological benefits. The literature has neglected romantic nostalgia—that is, nostalgia specifically for past experiences shared with one's partner—and its potential advantages for relationships. We examined romantic nostalgia in one correlational study, two experiments, and one daily diary study ( N = 638). Romantic nostalgia was positively associated with greater relationship commitment, satisfaction, and closeness (Study 1). Additionally, inducing romantic nostalgia via a writing task (Study 2) or music (Study 3) strengthened relational benefits. Finally, participants reported more positive relationship-specific experiences on days when they felt greater romantic nostalgia (Study 4). We discuss contributions to the nostalgia and relationships literatures.